2014
DOI: 10.1111/jdv.12449
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous adverse effects of BRAF inhibitors in metastatic malignant melanoma, a prospective study in 20 patients.

Abstract: Multiple cutaneous toxicities were observed in patients under BRAF inhibitors, mostly well controlled with adequate treatment. We recommend a multidisciplinary approach with regular assessments of the skin by a dermatologist. This allows early identification and adequate treatment to avoid premature discontinuation of a life-prolonging therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Among the 131 patients treated with vemurafenib over a 50‐month period in this cohort, 26% developed grade 3–4 severe skin toxicity leading to treatment discontinuation in 44% of cases. Our rate of all‐grade skin toxicity of 89% was consistent with the literature, while the rate of grade 3 rash of 19%, and of treatment discontinuation of 11% were higher than those usually reported . Permanent vemurafenib discontinuation is exceptional in clinical studies: no patient in Phase I and II studies and 1.5% of patients in Phase III studies due to rash, SJS, toxic epidermal necrolysis, cellulitis and flushing .…”
Section: Discussionsupporting
confidence: 89%
“…Among the 131 patients treated with vemurafenib over a 50‐month period in this cohort, 26% developed grade 3–4 severe skin toxicity leading to treatment discontinuation in 44% of cases. Our rate of all‐grade skin toxicity of 89% was consistent with the literature, while the rate of grade 3 rash of 19%, and of treatment discontinuation of 11% were higher than those usually reported . Permanent vemurafenib discontinuation is exceptional in clinical studies: no patient in Phase I and II studies and 1.5% of patients in Phase III studies due to rash, SJS, toxic epidermal necrolysis, cellulitis and flushing .…”
Section: Discussionsupporting
confidence: 89%
“…BRAF acts as an upstream signaler and promotor of cellular differentiation and proliferation in the mitogen‐activated protein kinase (MAPK) pathway. Inhibition of the wild‐type BRAF in non‐cancerous cells, such as keratinocytes, can lead to potentiated MAPK signaling (Vanneste et al, ). Potentiated MAPK signaling leads to prevention of apoptosis, excessive cell proliferation, and prolonged cell survival (Cohen, Bedikian, & Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 18 TCT drugs found 17.4% incidence of all-grade pruritus 108 . Alopecia can occur with BRAF (vemurafenib, dabrafenib) 109 and VEGFR inhibitors (sorafenib) 110 , albeit at significantly lower frequency than with conventional chemotherapy.…”
Section: Dermatologic Toxicitiesmentioning
confidence: 99%